2010
DOI: 10.1093/cvr/cvq032
|View full text |Cite
|
Sign up to set email alerts
|

Egr-1 deficiency in bone marrow-derived cells reduces atherosclerotic lesion formation in a hyperlipidaemic mouse model

Abstract: This study demonstrates that bone marrow-derived Egr-1 promotes macrophage accumulation, atherosclerotic lesion development, and lesion complexity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Amplification of the molecular changes in our mouse model of Achilles tendon injury is consistent with the amplified phenotypes observed in experimentally induced models for fibrosis, atherosclerosis, cardiac hypertrophy, and liver regeneration in Egr1 -/-mutant mice (44,(46)(47)(48)(49)(50)(51).…”
Section: Figuresupporting
confidence: 83%
“…Amplification of the molecular changes in our mouse model of Achilles tendon injury is consistent with the amplified phenotypes observed in experimentally induced models for fibrosis, atherosclerosis, cardiac hypertrophy, and liver regeneration in Egr1 -/-mutant mice (44,(46)(47)(48)(49)(50)(51).…”
Section: Figuresupporting
confidence: 83%
“…We find that miR-146 restrains vascular inflammation by repressing the NF-kB and EGR pathways, which play important roles in atherogenesis (Albrecht et al, 2010;Gareus et al, 2008;Harja et al, 2004). Additionally, miR-146a also targets TLR4 , which is expressed in several vascular and leukocyte cell types, and has been implicated in the etiology of atherosclerosis (den Dekker et al, 2010).…”
Section: Discussionmentioning
confidence: 65%
“…Several reports have indicated that Egr family members are induced by Dectin-1 ligands in macrophages and DCs (34,58) or neutrophils (59) in a calcineurin/NF-AT-dependent manner, which is likely also the case after Mincle stimulation. Although there are a number of reports on genes regulated by EGR family members in innate immune cells (60)(61)(62), the direct targets of EGRs in macrophages and DCs, especially in response to CLR activation, are currently unknown. We used expression of Egrs in this study primarily as a readout for early Mincle-dependent gene expression.…”
Section: Discussionmentioning
confidence: 99%